OP51 Experiences with and outcomes of advance care planning in bereaved relatives of frail older patients: a mixed methods study. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Overbeek, A; Korfage, I; Hammes, B; van der Heide, A; Rietjens, J
Abstract : Background: Advance Care Planning (ACP) may prepare relatives of frail older patients for future decision-making. Objective: To investigate (1) how bereaved relatives of frail older patients experience ACP conversations and (2) whether ACP has an effect on relatives' preparation for decision-making and on their levels of anxiety and depression. Design: Cluster randomised controlled trial. Setting: Residential care homes in the Netherlands. Subjects: Bereaved relatives of care home residents and community-dwelling frail older patients. Methods: We randomised 16 residential care homes to either the intervention group, where participants (frail older patients) were offered facilitated ACP, or the control group (n=201), where they received 'care as usual'. If participants died, we approached relatives for an interview. We asked relatives who had attended ACP conversations for their experience with ACP (open-ended questions). Furthermore, we compared relatives' preparation levels for decision-making and levels of anxiety and depression (HADS) between groups. This trial was registered (NTR4454). Results: We conducted interviews with 39/51 (76%) bereaved relatives (intervention group: n=20, control group: n=19). Relatives appreciated the ACP conversations. A few considered ACP redundant since they were already aware of the patient's preferences. Nine of 10 relatives in the intervention group felt adequately prepared for decision-making as compared to five of 11 relatives in the control group (p=.03). Relatives' levels of anxiety and depression did not differ significantly between groups. Conclusions: In our study, bereaved relatives of frail older patients appreciated ACP. ACP positively affected preparedness for decision-making. It did not significantly affect levels of anxiety or depression.